(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
The study aimed to show the impact of administrative ability on profit management practices and determine the concept and how to measure the value suitability of accounting information for the defect of companies in the Iraq Stock Exchange as well as to stand on the repercussions of profit management practices on the value suitability of accounting information and this research dealt with administrative ability as an independent variable represented by (sales, leverage, size, performance, market value) and profit management as a dependent variable that includes the profitability rate and its reflection on the value suitability of the information and a sample The study is a group of companies listed on the Iraq Stock Exchange using Excel and SPSS programs for statistical analysis, where the study found a statistically significant and significant presence among the study variables for the period from 2016 to 2024, indicating the extent of the impact of administrative ability on profit management practices and its reflection on the value suitability of accounting information with a positive relationship with a substantial moral impact between the study variables.